2009
DOI: 10.1038/pj.2009.324
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of isotactic poly(methyl methacrylate) thin films via self-organization and stereocomplex formation

Abstract: Morphological changes of macromolecularly porous thin films during isotactic (it) poly(methyl methacrylate) (PMMA) crystallization and the subsequent syndiotactic (st) poly(methacrylic acid) (PMAA) incorporation are described herein. Porous it-PMMA thin films were prepared on a gold substrate by the selective extraction of st-PMAA from stereocomplex films composed of it-PMMA/st-PMAA using layer-by-layer assembly. it-PMMA crystallization occurred when the porous it-PMMA films were immersed in a mixed solvent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Moreover, the solvent effects on the incorporation of st-PMAA into it-PMMA have been investigated in detail. 231 For example, when a mixed solvent (acetonitrile/water) is used, the crystallinity of it-PMMA increases as the water content increases, 232 interactions, 65 which can be harnessed for LbL assembly. 235,236 The alkaline hydrolysis of the stereocomplex PLLA/PDLA LbL films was quantitatively investigated using QCM, 237 and it was found that the stereocomplex is more readily hydrolyzed compared to crystalline polylactic acids (PLAs).…”
Section: Stereocomplexed Lbl Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the solvent effects on the incorporation of st-PMAA into it-PMMA have been investigated in detail. 231 For example, when a mixed solvent (acetonitrile/water) is used, the crystallinity of it-PMMA increases as the water content increases, 232 interactions, 65 which can be harnessed for LbL assembly. 235,236 The alkaline hydrolysis of the stereocomplex PLLA/PDLA LbL films was quantitatively investigated using QCM, 237 and it was found that the stereocomplex is more readily hydrolyzed compared to crystalline polylactic acids (PLAs).…”
Section: Stereocomplexed Lbl Assembliesmentioning
confidence: 99%
“…Moreover, the solvent effects on the incorporation of st-PMAA into it-PMMA have been investigated in detail. 231 For example, when a mixed solvent (acetonitrile/water) is used, the crystallinity of it-PMMA increases as the water content increases, 232 and this crystallization reduces the amount of st-PMAA incorporation. 233 Hollow LbL capsules (Figure 27) can be prepared with the stereocomplex (it-PMMA/st-PMMA) 10 .…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…As a consequence, the control of the stereoreglarity and of the molecular weight of it‐PMMA was realized by the template polymerization method using porous template films 124. We also cralified stability125–129 of the films and the polymerization mechanism using the porous it‐PMMA films in detail 130–132…”
Section: Stereocomplex Nanofilms and Their Biomedical Functionsmentioning
confidence: 99%
“…25 Furthermore, stereospecific template polymerization with a radical method was used to develop porous it-PMMA films, 26−29 although the template effect was limited in solution without any substrate. 30,31 Due to such an attracting phenomenon, we recently focused on the structural analysis of the porous it-PMMA film on substrates by AFM 32,33 and transmission X-ray diffraction (XRD) analyses. However, the available information was limited to wide-angle X-ray diffraction (WAXD).…”
Section: ■ Introductionmentioning
confidence: 99%